2019
DOI: 10.1002/app.48777
|View full text |Cite
|
Sign up to set email alerts
|

Design and fabrication of transdermal drug delivery patch with milliprojections using material extrusion 3D printing

Abstract: This paper investigates the effect of various 3D printing parameters on a transdermal drug delivery system with milliprojections printed using poly(lactic acid) (PLA). The parameters studied involve printing temperature, layer thickness, extrusion width, infill width, and nozzle orifice diameter. Their effects on the final print quality were evaluated based on the surface finish and dimensional accuracy of the milliprojections. The change in the molecular weights of the polymers after extrusion and printing su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…( a – c ) Microneedles produced by FDM technology. Reproduced with permission from [ 26 , 32 , 117 ], Royal Society of Chemistry, London, UK, 2018 ( a ), Springer Nature, Basingstoke, UK, 2020 ( b ), and John/Wiley & Sons, Inc., Hoboken, NJ, USA, 2020 ( c ). The image was created with Adobe Illustrator CC (Version 23.0.1.; Adobe Inc., San Jose, CA, USA, 2019).…”
Section: Fabrication Of Microneedles Using 3d Printing Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…( a – c ) Microneedles produced by FDM technology. Reproduced with permission from [ 26 , 32 , 117 ], Royal Society of Chemistry, London, UK, 2018 ( a ), Springer Nature, Basingstoke, UK, 2020 ( b ), and John/Wiley & Sons, Inc., Hoboken, NJ, USA, 2020 ( c ). The image was created with Adobe Illustrator CC (Version 23.0.1.; Adobe Inc., San Jose, CA, USA, 2019).…”
Section: Fabrication Of Microneedles Using 3d Printing Technologiesmentioning
confidence: 99%
“…It was found that a thinner layer led to a more accurate tip, and a thinner infill width resulted in more accurate part diameters. It was also reported that the smaller nozzle orifice and increased spacing between MNs produced better surface finish but had no significant effect on part accuracy [ 117 ].…”
Section: Fabrication Of Microneedles Using 3d Printing Technologiesmentioning
confidence: 99%
“…[1][2][3][4][5][6] Various 3D printing techniques such as vat polymerization-based printing technologies which include stereolithography (SLA), digital light processing (DLP) and PolyJet technologies, and powder-based printing technologies which include selective laser sintering (SLS), selective laser melting (SLM), and electron beam melting (EBM) have been developed for different materials and applications. [7][8][9][10] Among these technologies, the vat polymerization printing technologies are the most accurate printing processes with excellent surface finishing, making them the best choice for medical devices printing. However, parts printed by technologies such as SLA and DLP are less durable and robust as compare to the ones printed by the powderbased printing technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly in the medical field, 3D printing provides an effective solution for dentures, orthotic and prosthetic components, surgical models, and hearing aids 1–6 . Various 3D printing techniques such as vat polymerization‐based printing technologies which include stereolithography (SLA), digital light processing (DLP) and PolyJet technologies, and powder‐based printing technologies which include selective laser sintering (SLS), selective laser melting (SLM), and electron beam melting (EBM) have been developed for different materials and applications 7–10 . Among these technologies, the vat polymerization printing technologies are the most accurate printing processes with excellent surface finishing, making them the best choice for medical devices printing.…”
Section: Introductionmentioning
confidence: 99%
“…In their work, a simple, fast, and inexpensive step is introduced to fabricate polydimethylsiloxane microfluidic chips using enhanced internal scaffold removal. Tang et al 23 investigated the various 3D printing parameters on a transdermal drug delivery system with milliprojections printed using poly(lactic acid) (PLA). It was found that the smaller nozzle orifice and increased spacing between milliprojections produced better surface finish but had no significant effect on part accuracy.…”
Section: Introductionmentioning
confidence: 99%